Amit Jain’s new models for diabetic foot - Jain, Amit Kumar C. (International Surgery Journal, 2018)
Diabetes mellitus and its complications are growing worldwide. Diabetic foot is one such devastating complication often associated with amputation and mortality if not prevented. Various different specialists are involved in management of diabetic foot in form of multidisciplinary approach in view of lack of diabetic foot surgeons. The author proposes various new models for diabetic foot that are novel, visionary, practical and applicable in Asian countries like India where the education pattern is different from the west. These new concepts are addition to author’s Amit Jain’s system of practice for diabetic foot, which now is considered a modern diabetic foot surgery.